Rearranged (4 -> 2)-abeo-clerodane and clerodane diterpenes from Aristolochia chamissonis - Bomm, M. D.; Zukerman-Schpector, J.; Lopes, LMX (Elsevier B.V., 1999)
From stems of Aristolochia chamissonis Duch., five new diterpenes, one rearranged (4 --> 2)-abeo-clerodane and four ent-clerodanes, were isolated. Their structures were determined to be (+)-(4 --> 2)-abeo-kolavelool-3-oic acid, (-)-13-epi-2-oxokolavelool, (-)-2 beta-hydroxykolavelool, (-)-2 beta-hydroperoxykolavelool and (+)- 13-epi-2 alpha-hydroxykolavelool. In addition, lignans, sesquiterpenes, steroids and two known ent-clerodane diterpenes were isolated. (C) 1998 Elsevier B.V. Ltd. All rights reserved.
Keywords: Aristolochia chamissonis; Aristolochiaceae; diterpene; clerodane; rearranged (4 -> 2)-abeo-clerodane; lignans; sesquiterpenes; sitosterol; stigmastenone